2023
DOI: 10.1177/13623613231173056
|View full text |Cite
|
Sign up to set email alerts
|

Re-examining the association between the age of learning one is autistic and adult outcomes

Abstract: It was recently reported that learning one is autistic earlier in life is associated with greater quality of life and well-being in university students. In a pre-registered extension of this work, we addressed several limitations of this study by (a) recruiting a larger sample of more diverse ages and education levels, (b) distinguishing between learning about and receiving an autism diagnosis, (c) accounting for additional confounding variables, and (d) studying different quality of life dimensions. Autistic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…For example, Oredipe et al (2023) spoke to 78 Autistic university students using an online survey about when and how they found out they were Autistic and found that, while participants who learned they were Autistic at a younger age had higher quality of life and wellbeing in adulthood, participants who learned they were Autistic at an older age had more positive initial reactions about being Autistic. Leung et al (2023), however, failed to find a significant relationship between the age of learning one was Autistic and well-being when Autistic traits were accounted for. Riccio et al (2021) examined the impact of how one's autism was disclosed to them (i.e., voluntary versus involuntary parental disclosure) and found that adolescents whose parents voluntarily disclosed their autism diagnosis to them were more positive about being Autistic than those whose parents involuntarily disclosed.…”
Section: Introductionmentioning
confidence: 84%
“…For example, Oredipe et al (2023) spoke to 78 Autistic university students using an online survey about when and how they found out they were Autistic and found that, while participants who learned they were Autistic at a younger age had higher quality of life and wellbeing in adulthood, participants who learned they were Autistic at an older age had more positive initial reactions about being Autistic. Leung et al (2023), however, failed to find a significant relationship between the age of learning one was Autistic and well-being when Autistic traits were accounted for. Riccio et al (2021) examined the impact of how one's autism was disclosed to them (i.e., voluntary versus involuntary parental disclosure) and found that adolescents whose parents voluntarily disclosed their autism diagnosis to them were more positive about being Autistic than those whose parents involuntarily disclosed.…”
Section: Introductionmentioning
confidence: 84%
“…A complicating factor and potential limitation of this study is that not all participants knew themselves that they were autistic while working in schools, and although research indicates that sharing a diagnosis at work does not always feel safe for autistic people in the school sector (Wood & Happé, 2021) and elsewhere (Romualdez et al, 2021), it may be that this information could have helped the participants in this study at the time. It is also not clear whether late diagnosis per se has a negative impact on individual outcomes (Leung et al, 2023). Furthermore, the growth of the neurodiversity movement, which posits, inter alia, strengths-based approaches to disability and difference (den Houting, 2019), is potentially sowing the seeds for better understanding of autistic and otherwise neurodivergent school staff across a range of work sectors.…”
Section: Conc Lusionmentioning
confidence: 99%
“…He added that this made him react aggressively: "Only in fth grade did I agree, or sixth grade -I nally agreed to listen". Emma (27) who was told at age 16, said: "At rst, I felt so uneasy that I said, I don't have it. I think it was hard for me to accept… my diagnosis because it's hard to be different".…”
Section: Child's Post-disclosure Reactionsmentioning
confidence: 99%
“…Oredipe et al (2022) examined the effects of autism disclosure on well-being and quality of life (QoL) in a sample of autistic university students, and found disclosure at a younger age was associated with higher well-being and QoL. In contrast, Leung et al (2023) examined a more sociodemographically diverse sample of autistic adults, and found that age of disclosure did not predict QoL and well-being in adulthood. Rather, having more autistic traits was a strong predictor of poorer outcomes.…”
Section: Introductionmentioning
confidence: 99%